Wife’s Reclaiming from her Husband What She Spends on Herself in Islamic Jurisprudence and Jordanian and Emirati Personal Status Laws - Alzyadat, Emad Abdel Hafiz Ali; Alemoush, Mohammad Mahmoud; Al Ghananim, Kathafi Izzat Abdel Hadi (Dirasat: Shari’a and Law Sciences, 2025)
Objectives: This study aims to provide an explanation of the wife’s ruling on recourse to her husband for what she spent on herself from her own money, or borrowed in Islamic jurisprudence and Jordanian and Emirati personal status laws. Methods: The issue was studied through two approaches: The analytical approach, by analyzing the sayings of jurists and their evidence on the issue, and the comparative approach to compare between the schools of thought of jurists and the specific legal texts on the issue. Results: The study concluded that a husband must provide for his wife, whether in times of ease or hardship. If he fails to do so and his wife fulfills this obligation on his behalf, she has the right to seek reimbursement from him, provided they mutually agreed on this arrangement or a court ruled in favor of the maintenance. However, her claim for reimbursement is contingent upon this agreement or legal ruling and cannot be made before such steps are taken. Conclusion: The Islamic jurisprudential schools agreed on the wife’s right to seek reimbursement from her husband for what she spent on herself. However, they differed regarding the circumstances in which this right is established and when it is forfeited. Consequently, personal status laws varied in their details, depending on the school of thought each law adopted. The study recommends conducting comparative jurisprudential research on personal status laws, particularly in the nuanced aspects related to family matters.